Synthesis and Structure of [Et3NH][Fe(HL)2] [H3L = L‐2‐(3, 5‐Di‐tert‐butyl‐2‐hydroxybenzylamino)succinic Acid] and Its Catalytic Activity towards Efficient Photodegradation of Dyes in the Presence of H2O2. Issue 30 (5th September 2014) - Dasgupta, Sohaham; Atta, Sanghamitra; Singh, N. D. Pradeep; Deb, Dibakar; Kassel, W. Scott; Bhattacharjee, Manish
Abstract: A new biogenic potentially tetradentate ligand, L ‐2‐(3, 5‐di‐ tert ‐butyl‐2‐hydroxybenzylamino)succinic acid, has been synthesized. Upon reaction with FeCl3 in the presence of triethylamine, it afforded the complex [Et3 NH][Fe(HL)2 ] (1 ). The complex was structurally characterized and was used for homogeneous photocatalytic degradation of methylene blue (MB), malachite green (MG), crystal violet (CV) and rhodamine B (RhB) under visible‐light irradiation in aqueous solution in the presence of H2 O2 . Abstract : A new biomimetic amino acid ligand, L ‐2‐(3, 5‐di‐ tert ‐butyl‐2‐hydroxybenzylamino)succinic acid (LH3 ), and its iron(III) complex, [Et3 NH][Fe(LH)2 ], have been synthesized. The complex was structurally characterized. The complex was found to be an efficient catalyst for the environmentally friendly visible‐light‐mediated degradation and decolouriation of a number of dyes such as methylene blue.